Intravenous Single-dose Toxicity of Mountain Ginseng Pharmacopuncture in Sprague-Dawley Rats - Kwangho Lee; Seungho Sun; Junsang Yu; Chungsan Lim; Kirok Kwon (Korean Pharmacopuncture Institute, 2014)
Objectives: Mountain ginseng pharmacopuncture (MGP) is an extract distilled from either mountain cultivated ginseng or mountain wild ginseng. This is the first intravenous injection of pharmacopuncture in Korea. The word intravenous does not discriminate between arteries, veins, and capillaries in Oriental Medicine, but only the vein is used for MGP. The aim of this study is to evaluate the intravenous injection toxicity of MGP through a single-dose test in Sprague-Dawley (SD) rats. Methods: Male and female 6-week-old SD rats were injected intravenously with MGP (high dosage of 20 mL/kg or low dosage of 10 mL/kg). Normal saline was injected into the rats in the control group by using the same method. After the rats has treated, we conducted clinical observations, body-weight measurements and histological observations. Results: In this study, no mortalities were observed in any of the experimental groups. Also, no significant changes by the intravenous injection of MGP were observed in the body weights, or the histological observations in any of the experimental groups compared to the control group. The lethal dose for intravenous injection of MGP was found to be over 20 mL/kg in SD rats. Conclusion: Considering that the dosage of MGP generally used each time in clinical practice is about 0.3 mL/kg, we concluded with confidence that MGP is safe pharmacopuncture.